To disguise the truth - Turano, Jen (Turano, Jen. Bleecker Street Inquiry Agency, 2022)
"When Arthur Livingston seeks out the agency to find a missing heiress, Eunice Holbrooke realizes her past has finally caught up with her. In order to avoid Arthur and conceal her real identity, Eunice goes undercover on another case. But will the truth she uncovers set her free or place her-and her heart-in peril's way?"--